Tardive Dyskinesia‐like Syndrome Due to Drugs that do not Block Dopamine Receptors: Rare or Non‐existent: Literature Review - D’Abreu, Anelyssa (Tremor Other Hyperkinet Mov (N Y), 2018)
BACKGROUND: Although tardive dyskinesia (TD) is most commonly defined as a movement disorder caused by chronic exposure to dopamine‐receptor‐blocking drugs (DRBDs), it has also been thought to result from exposure to some non‐DRBDs. METHODS: We critiqued many reviews making the association between non‐DRBDs and a TD‐like syndrome and almost all case reports. We checked whether cases met criteria for the diagnosis of TD‐like syndrome and whether DRBDs had been excluded. RESULTS: We found that both tricyclic antidepressants and selective serotonin reuptake inhibitor antidepressants may unmask or exacerbate TD after prior exposure to or with concurrent use of DRBDs. We found support for its existence outside of this context to be extremely weak. DISCUSSION: There is little evidence that drugs other than DRBDs by themselves cause a TD syndrome; most reported cases appear to occur as a result of a “priming” effect induced by a DRBD, which is later unmasked.